In Vitro Analysis of FSH- and LH-Induced Alterations in Progesterone Levels in Human Granulosa–Theca Cells - Coskun Akcay, Neslihan; Gunes, Ali Can; Zirh, Selim; Bozdag, Gurkan; Mumusoglu, Sezcan; Portakal Akcin, Oytun; Muftuoglu, Sevda Fatma; Karakoc Sokmensuer, Lale (The European Research Journal, 2026)
Objectives: This study aimed to evaluate whether administration of luteinizing hormone (LH) before the ovulation trigger could modulate elevated progesterone levels. Methods: Human granulosa-theca tissues were obtained from 15 women aged 18–38 years undergoing laparoscopic ovarian cystectomy at the Department of Gynecology and Obstetrics, Hacettepe University. The tissues were cultured in vitro and treated with 12.5 mIU/mL recombinant follicle-stimulating hormone (r-FSH; Group A), 18.75 mIU/mL r-FSH (Group B), or 18.75 mIU/mL r-FSH plus 6.25 mIU/mL recombinant LH (r-LH; Group C). Baseline and post-treatment estradiol (E2) and progesterone concentrations were measured at 0, 24, and 48 hours. Immunofluorescence staining for aromatase, cytochrome P450, and Ki67 was performed to assess steroidogenic activity and cellular proliferation. Results: A mild trend toward reduced progesterone and increased E2 levels was observed following LH supplementation at both time points; however, these changes did not reach statistically significant. No statistically significante differences were observed in progesterone or E2 levels among the treatment groups at 24 h (P=0.891 and P=0.805, respectively) or 48 h (P=0.878 and P=0.505, respectively). Expression levels of aromatase, cytochrome P450, and Ki67 did not differ significantly between groups at 24 h (P=0.665, P=0.932 and P=0.953, respectively) or 48 h (P=0.911, P=0.674 and P=0.202, respectively). Conclusions: These findings suggest that although r-LH addition to high-dose r-FSH does not significantly alter progesterone synthesis, it may exert a subtle regulatory effect on steroidogenesis. Larger studies with extended culture durations are needed to further elucidate the biological and clinical significance of these observations.